Towards a common transatlantic strategy in dealing with Russia? - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2008)
The conflict over Georgia has had one positive implication: the United States and Europe are forced to think strategically in dealing with Russia. Since the end of the cold war, Russia - and this is sometimes hard to understand for Europeans - has had little salience to US foreign policy. The selective cooperation on nonproliferation issues and on fighting transnational terrorism does not amount to a strategic policy. For the Europeans, despite the higher importance attached to Russia, developing a common policy was never easy, but has become more difficult because of EU enlargement to the East. Although the EU and the United States have shown a rather high degree of unity in the immediate response to the crisis over Georgia, we are still far away from a transatlantic convergence of perceptions, interests, and preferred strategic approaches in reacting to an assertive Russia
Keywords: 320